TERMINAL DE TRANSPORTES PARA MEJORAR LA MOVILIDAD EN GUAMAL META (2021)
The purpose of this degree project is Design a road transport terminal in the Municipality of Guamal that allows organizing activities related to this type of infrastructure. In the Municipality, 60% of the population travels daily to Acacias and Villavicencio for work and study reasons, therefore, an analysis is carried out on the main roads that connect the Municipality of Guamal with the capital of Meta and the flow so that through this is achieved by relocating the transport terminal in a strategic place. Achieve the relationship of the intervened points through public spaces and cycle routes that allow easy access from the community to different parts of the municipality.